Contribution of perforated steel ribs to load-carrying capacities of steel and concrete composite slabs under negative bending. Issue 12 (September 2018) - Xu, Xiaoqing; Liu, Yuqing; Zuo, Yize
To attain a better understanding of the contribution of perforated steel ribs to the load-carrying capacities of steel and concrete composite slabs, six specimens with different shear connectors and areas of steel bars were tested under negative bending. Applied load, deformation, location and subsequent trajectory of cracks, strains, and failure mode of each specimen were recorded during the tests. Shear cracks were observed in two specimens, while in the other specimens only bending cracks were found. The perforated L-shaped ribs were proved to reduce the shear crack risk of composite bridge deck slabs and have a larger contribution to the loading-carrying capacities of composite slabs than plain ribs. Based on the experimental results, calculation methods were proposed to evaluate the flexural and shear strength of composite slabs. The calculated methods can quantitatively show the favorable influence of perforated steel ribs on the loading-carrying capacities of composite slabs, and the failure modes can be well predicted.